The effect of enterprise and household credit on economic growth and real exchange rate dynamics: Evidence from SEE countries - Tijana Angjelkovska; Egzona Hani; Milan Eliskovski (National Bank of the Republic of Macedonia, 2016)
In this paper, we empirically assess the effects of the decomposed private sector credit on the economic growth and real effective exchange rate (REER) dynamics, for eight SEE countries. We construct dataset for Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Macedonia, Romania, Serbia and Turkey, for the period 1995-2014 with quarterly frequency by decomposing bank credit into households and enterprises so that we can assess their effects on both, the economic growth and REER. The empirical findings are based on panel data models. We find that enterprise credits are positively related with economic growth, whereas for the household credits the result is ambiguous. Regarding the impact of the decomposed credit on the REER, used as a measure of the price competitiveness of the specific countries, our findings suggest that both household and enterprise credits contribute to appreciation of the REER. However, unlike the theory, our findings did not show significant difference on the magnitude of the different credits on the appreciation.
Keywords: E44; E51; 330; household credit growth; enterprise credit growth; economic growth; REER; South-East Europe